Reduzierung des Zuckerkonsums für eine bessere Mundgesundheit – Welche Strategien sind Erfolg versprechend? - Heilmann, Anja (Bundesgesundheitsblatt Gesundheitsforschung Gesundheitsschutz, 2021)
Health promotion strategies can make a significant contribution to the prevention of non-communicable diseases. The most important non-communicable diseases affecting the mouth and teeth are dental caries and periodontal disease. Sugar is a causal factor in the development of dental caries, obesity and obesity-related diseases. Sugar is therefore recognised as an important commercial determinant of health and a public health priority. However, existing strategies to reduce sugar consumption often focus on individual behaviour change while ignoring the role of the wider social and commercial environment. In this article we describe the current recommendations on sugar intake made by the World Health Organization, existing data on sugar intake in Germany as well as the social and commercial factors that influence sugar consumption. Important public health principles will be outlined, followed by a discussion of appropriate sugar reduction strategies. Examples for upstream and downstream approaches to prevention are presented and opportunities for dental health professionals to influence policy and practice highlighted.